The dietary changes during Ramadan and their impact on anthropometry, blood pressure, and metabolic profile - Al-Jafar, Rami; Yuqi, Wang; Elliott, Paul; Tsilidis, Konstantinos K.; Dehghan, Abbas (Frontiers in Nutrition, 2024)
Background-The effect of Ramadan intermittent fasting(RIF) on the metabolic profile, anthropometry and blood pressure has been investigated in multiple studies. However, it is still unknown to what extent changes in nutrient intakes contribute to these changes.Methods-This observational study was conducted in London (UK) in 2019. The study collected diverse data from a community-based sample in London before and during/after Ramadan. Collected data included a 3-day food diary (before and during Ramadan), as well as blood samples, anthropometric measurements and blood pressure (before and after Ramadan). The food diary was translated into nutritional data using nutrition software "Nutritics". The changes in nutrient intakes were investigated using a mixed-effects regression model. The impact of adjusting for nutrient intake change was investigated on the absolute difference of metabolites (Nightingale platform), systolic/diastolic blood pressure and anthropometric measures.The study collected data on food intake before and during Ramadan from 56 participants; the mean age was 44.7 ± 17.3, and 51.8% (n= 29) were females. We found a change in the intake of 11 nutritional factorsmicronutrients, glucose, fructose, betaine, sugars, sugars as monosaccharide equivalents, lutein/zeaxanthin, starch, starch as monosaccharide equivalents, proline, glutamic acid and lycopene. No changes in quantities or proportions of macronutrients, carbohydrates, protein and fat. Mainly, the changes in diet during Ramadan are characterised by more consumption of sugars(62%,P<0.001) and a lower intake of starch(-21%,P=0.012). The changes in14 metabolite levels (two glycolysisrelated metabolites, one amino acid, two ketone bodies, two triglyceride, six lipoprotein subclasses, and an inflammation marker) after Ramadan were partially associated with some changes in nutrient intakes during Ramadan, especially betaine, fructose, glucose, starches and sugars. The lutein/zeaxanthin intake change explained inversely 14% of systolic blood pressure changes. Moreover, BMI and weight changes were partially explained by changes in intake of fat(7%;9%), monounsaturated fat (6%; 7%), starch (8%; 9%), and starch as monosaccharide equivalents(8%;9%) intakes in a direct relationship.Ramadan were associated partially with the observed changes in the metabolic profile, blood pressure and anthropometry. This confirms the changes associated with RIF in the metabolic profile, blood pressure and anthropometry are not an absolute physiological response to the diet transition occurring during Ramadan.